2016
DOI: 10.1155/2016/7639842
|View full text |Cite
|
Sign up to set email alerts
|

A 12-Week Vigorous Exercise Protocol in a Healthy Group of Persons over 65: Study of Physical Function by means of the Senior Fitness Test

Abstract: The aim of this study was to assess the effects of vigorous exercise on functional abilities by means of a Senior Fitness Test (SFT) in a group of elderly adults. Twenty healthy and inactive people performed vigorous exercise (VE: 12 men and 8 women, aged 69.6 ± 3.9 years). At the beginning of the study (T0) and after 3 months (T1), each subject's functional ability was tested for muscular strength, agility, cardiovascular fitness, flexibility, and balance. The VE was designed with continuous and interval exer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
19
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(25 citation statements)
references
References 20 publications
(25 reference statements)
3
19
0
3
Order By: Relevance
“…The obtained results might be compared to those of other studies involving training with aerobic and resistance exercises among older people. As observed in this research, the main time effects of marching training for both the EG and the CG on strength, endurance and agility are similar to those of other studies in which mixed exercise programs were employed [10,25,[27][28][29].…”
Section: Discussionsupporting
confidence: 88%
“…The obtained results might be compared to those of other studies involving training with aerobic and resistance exercises among older people. As observed in this research, the main time effects of marching training for both the EG and the CG on strength, endurance and agility are similar to those of other studies in which mixed exercise programs were employed [10,25,[27][28][29].…”
Section: Discussionsupporting
confidence: 88%
“…Exercise has been reported as a very important factor in the maintenance of good health [31][32][33]. Todde et al [33] has suggested that high-intensity exercise and functional exercises can improve functional mobility and muscle endurance among those who are above the age of 65.…”
Section: Exercisementioning
confidence: 99%
“…Despite there are a lot of positive indicators about the relationship between active lifestyle and health (such as better control of dyslipidemia, improvement of diabetes, obesity, BP, among others), the sedentary behavior is prevalent in the population [14,19] . Moreover, among the elderly who practice physical exercise, the most of them prefer to practice the exercise independently, without supervision (no control of intensity, duration and frequency), which can represent no positive effect for health [19,20] .…”
Section: Resultsmentioning
confidence: 99%